DISC1 Regulates Mitochondrial Trafficking in a Miro1-GTP-Dependent Manner - Norkett, Rosalind; Lesept, Flavie; Kittler, Josef T. (Frontiers in Cell and Developmental Biology, 2020)
The disrupted in schizophrenia 1 (DISC1) protein is implicated in major mental illnesses including schizophrenia and bipolar disorder. A key feature of psychiatric disease is aberrant synaptic communication. Correct synaptic transmission is dependent on spatiotemporally regulated energy provision and calcium buffering. This can be achieved by precise distribution of mitochondria throughout the elaborate architecture of the neuron. Central to this process is the calcium sensor and GTPase Miro1, which allows mitochondrial trafficking by molecular motors. While the role of Miro1-calcium binding in mitochondrial transport is well described, far less is known regarding the functions of the two GTPase domains. Here, we investigate the effects of a psychiatric disease-associated mutation in DISC1 on mitochondrial trafficking. We show that this DISC1 mutation impairs Miro1’s ability to transport mitochondria. We also demonstrate the necessity of the first Miro1 GTPase domain in determining direction of mitochondrial transport and the involvement of DISC1 in this process. Finally, we describe the effects of mutant DISC1 on positioning of mitochondria at synapses.